Information Technology: The Change Agent for Paradigm of Education - with Special Reference to Indian Conditions - R., Professor Anupama; Bansal, Prof. (Dr.) Sanjeev (Prabandhan: Indian Journal of Management, 2012)
Information Technology is a great driver of change and re-engineering. With IT, unchartered territories can be covered and new heights scaled. Increased communication, speed in transactions, accuracy in administrative tasks and collaboration amongst team members are the obvious advantages. The implementation of IT has gone much, much beyond - Elearning, virtual classrooms, IP Cameras enabling archives of surveillance; global connectivity of classrooms in case of guest lectures are only some of the initiatives. This study traces evolution and implementation of IT. It also studies the difficulties faced and solutions worked out till optimum scenarios are reached. It also emphasizes on the changing teaching-learning pedagogies and the impact IT-enabled processes has on the students. Both advantages and fallouts are discussed, and it poses to the readers the question of an optimum mix of IT enabled and traditional academics. Security aspects were another area of concern, be it intellectual and copyrights of professors when they upload their lectures on the intranet or integrity of databases. The paper traces the impact IT is having on the teaching-learning scenarios across the world, with special reference to India. The areas of inequality of acceptance and use are discussed, especially the parameters of gender, culture and physical inabilities. Various tools of IT implementation such as blogs, podcasts, weblogs, discussion forums have been studied. Again, emerging trends such as Virtual Learning Environments, Weblogs, edutainment, learning ware, group ware, Group Support Systems, etc. are highlighted. It also tries to understand the barriers faced by educators, students and administrators in acceptance of IT enabled teaching - learning platforms. The essential balance between content and technology has to be maintained. Certain educational, economical and technical pre-requisites are mulled upon.